SLEEP DISTURBANCES IN MAJOR PSYCHIATRIC DISORDERS – PREVALENCE, MECHANISMS AND TREATMENT – A NARRATIVE REVIEW - Anna Maria Gęsińska; Krystian Czyżykowski; Helena Szelka; Bartosz Golis; Paweł Edyko; Alicja Babula; Wiktor Golus; Katarzyna Andrzejewska; Zuzanna Przybyła; Hubert Woźniak (International Journal of Innovative Technologies in Social Science, 2025)
Sleep disturbances are among the most prevalent and disabling symptoms across major psychiatric disorders, yet they remain underrecognized and undertreated. This review synthesizes findings from 43 peer-reviewed studies published between 2008 and 2025, examining the prevalence, neurobiological mechanisms, and treatment of sleep abnormalities in major depressive disorder (MDD), bipolar disorder (BD), schizophrenia (SCZ), and post-traumatic stress disorder (PTSD). Across disorders, insomnia is the most frequent disturbance, affecting up to 80% of patients with MDD and nearly 90% of those with PTSD. Other recurrent abnormalities include hypersomnia during depressive phases of BD, circadian rhythm misalignment, and fragmented sleep in SCZ. Neurobiological evidence implicates dysregulation of the circadian system, hyperactivity of the hypothalamic–pituitary–adrenal axis, orexin signaling imbalance, and neuroinflammatory processes as shared mechanisms underlying psychiatric sleep pathology. Effective management requires a multimodal approach. Cognitive behavioral therapy for insomnia (CBT-I) demonstrates robust efficacy across disorders, improving both sleep and psychiatric outcomes. Pharmacological interventions—such as dual orexin receptor antagonists, melatonin agonists, and sedating psychotropics—show moderate benefits but require careful monitoring. Chronotherapeutic and neuromodulatory strategies (e.g., light therapy and noninvasive brain stimulation (NIBS) represent promising adjuncts for circadian stabilization. Overall, sleep disturbances emerge as transdiagnostic phenomena that both reflect and exacerbate psychiatric pathology. Early identification and targeted treatment of sleep problems may enhance therapeutic response, reduce relapse risk, and improve overall functioning. Integrating systematic sleep assessment into routine psychiatric care is essential for achieving comprehensive, recovery-oriented treatment.